2010
DOI: 10.1088/0004-637x/713/1/257
|View full text |Cite
|
Sign up to set email alerts
|

SUZAKUOBSERVATION OF GRS 1915+105: EVOLUTION OF ACCRETION DISK STRUCTURE DURING LIMIT-CYCLE OSCILLATION

Abstract: We present results from the Suzaku observation of the microquasar GRS 1915+105 performed during the 2005 October multiwavelength campaign. The data include both stable state (class χ) and limit-cycle oscillation (class θ). Correct interstellar absorption as well as effects of dust scattering are fully taken into account in the spectral analysis. The energy spectra in the 2-120 keV band in both states are all dominated by strong Comptonization of disk photons by an optically thick (τ ≈7-10) and low temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 44 publications
9
77
0
Order By: Relevance
“…The values of γ min and Γ, which were free to vary during first sets of fitting, were found to maintain almost constant values (γ min : mean 1.3, rms 0.7; Γ: mean 4.6, rms 1.6) in all the observations and in the various segments and were then fixed to their average values. The γ min closely agrees with the results obtained by Zdziarski et al (2005) for the analysis of RXTE+OSSE observations, while, Γ is fixed to a value slightly larger or marginally compatible with those from previous measurements (Zdziarski et al 2005;Ueda et al 2010).…”
Section: Spectral Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…The values of γ min and Γ, which were free to vary during first sets of fitting, were found to maintain almost constant values (γ min : mean 1.3, rms 0.7; Γ: mean 4.6, rms 1.6) in all the observations and in the various segments and were then fixed to their average values. The γ min closely agrees with the results obtained by Zdziarski et al (2005) for the analysis of RXTE+OSSE observations, while, Γ is fixed to a value slightly larger or marginally compatible with those from previous measurements (Zdziarski et al 2005;Ueda et al 2010).…”
Section: Spectral Analysissupporting
confidence: 89%
“…The detection of a fluorescence Kα iron line from GRS 1915+105 has been reported on several occasions (Martocchia et al 2002;Zdziarski et al 2005;Martocchia et al 2006;Ueda et al 2010) and, more recently, by Titarchuk & Seifina (2009). In particular, Martocchia et al (2002) from the detection of a strong line found evidence of relativistic effects in a black hole environment.…”
Section: The Iron Linementioning
confidence: 92%
See 3 more Smart Citations